Five new Erythrina alkaloids from the stems of Erythrina corallodendron. Issue 5 (4th May 2022) - Cai, Yun-Shuang; Li, Yu-Tong; Fu, Jiang; Chen, Zhao-Chan; Wang, Yang; Li, Yong; Yu, Shi-Shan
Abstract: Five new Erythrina alkaloids and five known E. alkaloids were isolated from a 95% ethanol extract of the stems of Erythrina corallodendron L. Their chemical structures were elucidated by UV, IR, HRESIMS, NMR and X-ray. Furthermore, the analgesic activities of E. alkaloids 1, 2 and 6 were evaluated by using an acetic acid-induced writhing test in mice, and their writhing inhibition rates were 67.9%, 64.6% and 70.3% at doses of 20 mg/kg, respectively. Graphical Abstract: UF0001